Modeling the crack interference in X80 oil and gas pipeline weld - Cui, Wei (2023)
Based on the numerical simulation method of the virtual crack closure technique (VCCT), an interference model was established to investigate the physical problem of two interacting cracks of different sizes in the welding zone of oil and gas pipelines. The obtained results of the current interference problem were compared with those of single crack case. Various crack configurations, such as different crack spacing and different crack sizes, were analyzed. The characteristic quantity fluid pressure load P during the crack propagation process, the peak value of the von Mises stress distribution field of the crack growth path, as well as the difference ∆Bx between the peak value of the magnetic induction intensity component at the crack and the value of the magnetic induction intensity component at its symmetrical position were calculated. The crack interaction scale factors, including γP, γMises, and γΔBx, were compared and analyzed. The numerical modeling results show that when the unequal-length double cracks interfere with each other, the cracks are more likely to propagate toward each other. The tendency of the double-cracks to propagate toward each other gradually weakens as the distance between the crack tips increases and is finally the same as that of single-crack cases. It was also found that the effect of large-sized cracks on small-sized cracks is greater than that of small-sized ones on large-sized ones. The numerical modeling results could be applied for the prediction and analysis of multicrack damage in oil and gas pipeline welds.